Los programas de tv para el desarrollo emotivo de los niños de 4 a 6 años de la escuela “Juan Montalvo” de la parroquia Vilcabamba - Jiménez Rojas, Juan Ramiro (2016)
This thesis deals with: TV PROGRAMS FOR EMOTIONAL DEVELOPMENT OF CHILDREN 4 TO 6 YEARS SCHOOL "JUAN MONTALVO" PARISH VILCABAMBA. It was structured and developed in accordance with Regulation of the current Academic Board at the National University of Loja. The central problem of the research is How to apply a learning strategy for television programs and the emotional development of parents and children it was proposed as general objective: To determine the impact of TV programs in the emotional development of children 4 to 6 years of school Juan Montalvo of Vilcabamba parish. The methods used for the preparation of this research work were: scientific, inductive-deductive, descriptive, analytical, statistical model that served them help with the proposed goal efficiency. The techniques and instruments used were: surveys of students and parents of children aged 4 to 6 years of children investigated. In this graph, 18% of children like to watch TC, 61.24% of the children see GamaTV, the 20,40% see Ecuavisa. Among the observations showed us that children also watch channels like Disney Chanel. However it is significant that no child is interested in Ecuador TV show, but no child sees it. In this graph the favorite programs for children are 22.44% like to see novels, the 48.93% cartoon, 12.24%, 8.16% educational channel, 10, 23% movies. In the graph shows that 8.16% watch TV daily hours, two hours 24.48%, 42.8% three hours, 24.48% more than three hours a day. This graph shows that 48% of children watch television with their parents and 20% see it alone.